(3CLhHI GdbGVi GdfYeGf Hf eMeO GdeZQHjs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfg hUd cJGHc fSCd ajg GdLhGH Yf eSGFd s
(3BNQgG (B:s
(3dGjfcM GdeQCI EdG hdjgG aEf ZGH GfJXQ QLhYg s
(3hgj CLhHI dCSFdI abgjI SCdg YfgG NWGH Hf hSje ebOe RhGhI hMceges
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
Keywords: (3eJaQbGJs